STATE SUPPORT OF YOUTH ENTREPRENEURSHIP IN RUSSIA AND RUSSIAN REGIONS - A. Eremeeva, E.; V. Volkova, N.; V. Khalilova, T. (Gênero & Direito, 2019)
The article is devoted to the analysis of support for youth entrepreneurship in Russia and Russian regions. Consideration of this topic is relevant, since, on the one hand, the interest of Russian youth in creating a business is growing, and on the other, society and the state are interested in young, initiative entrepreneurs. The article reviews, analyzes and compares the state support for young businessmen at the federal and regional levels. The main research methods are comparative analysis, analysis of regulatory legal acts of Russia and regions of the Russian Federation, systematization and generalization of legal information. The result of the study was the conclusion on the implementation of support for young entrepreneurs in the Russian Federation and its feasibility. The main problems of this direction of support were highlighted. So, some discrepancies in federal and regional legislation, inaccuracies in the organization of the assistance process itself, the lack of a clear plan of measures to support this type of business, etc. were revealed. Recommendations were also proposed that will help to overcome these problems and make the support of young entrepreneurs more accessible, appropriate and effective. So, for example, it was proposed to simplify the very concept of youth entrepreneurship, to fix at the federal level the main directions of its support, etc.